Spleno-Mesenteric Venous Blood Flow Dynamics in Adult Patients with Chronic Portal Vein Thrombosis Analyzed by Sequential CT-Spleno- and Mesenterico-Portography - Alexandra Schlitt; Andrea Goetz; Christian Stroszczynski; Florian Zeman; Christina Hackl; Hans J. Schlitt; Ernst-Michael Jung; Wibke Uller; Simone Hammer (Life)
Background: Portal vein thrombosis (PVT) leads to portal hypertension (PH) with its sequelae. Computed tomography spleno-mesenterico-portography (CT-SMPG) combines sequential CT spleno-portography and CT mesenterico-portography. CT-SMPG comprehensively illustrates the venous hemodynamic changes due to PH. Objective: To assess the effects of PV confluence thrombosis (PVCT) and liver cirrhosis on venous blood flow characteristics of patients with PVT. Method: CT-SMPG was performed in 21 patients with chronic PVT. CT-SMPG was compared to standard contrast-enhanced CT (CECT) and gastroscopy concerning the patency of splanchnic veins, varices and venous congestion. Results: PVCT had a significant effect on perfusion patterns: in patients without PVCT, esophageal varices (EV) and gastric varices were supplied by either the splenic vein (SV), the superior mesenteric vein (SMV), or both. In patients with PVCT, EV and gastric varices were mostly supplied by the SV (p = 0.021, p = 0.016). In patients without PVCT, small bowel varices were fed by both systems or the SMV, while in patients with PVCT they were fed by the SMV (p = 0.031). No statistically significant changes were detected regarding gastropathy, colorectal varices and small bowel congestion. Liver cirrhosis had no statistically relevant effect on hemodynamics. Conclusions: In CT-SMPG, patients with PVCT showed different venous hemodynamics to patients without PVCT, and this can serve as a basis for selecting therapy options.